2020
DOI: 10.1177/0969141320973060
|View full text |Cite
|
Sign up to set email alerts
|

Quality measures of a multicentre universal newborn hearing screening program in Malaysia

Abstract: Objective To evaluate and discuss the outcomes of the universal newborn hearing screening program conducted at four public hospitals in Malaysia. Method A retrospective analysis of the universal newborn hearing screening database from each hospital was performed. The database consisted of 28,432 and 30,340 screening results of babies born in 2015 and 2016, respectively. Quality indicators (coverage rate, referral rate, return for follow-up rate, and ages at screening and diagnosis) were calculated. Results Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Sixteen studies that reported a two-stage hearing screening protocol, employed OAE (TE/DP-OAE) or AABR as screening tests (individually or combined in either stage) 17–31. The other 25 studies used only OAEs (DP/TE)32–49 or AABR screening50 51 for testing in both stages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen studies that reported a two-stage hearing screening protocol, employed OAE (TE/DP-OAE) or AABR as screening tests (individually or combined in either stage) 17–31. The other 25 studies used only OAEs (DP/TE)32–49 or AABR screening50 51 for testing in both stages.…”
Section: Resultsmentioning
confidence: 99%
“…Audiologists were the primary screening personnel in many newborn and infant programmes,17 30 34 38 44 48 54 59 61 62 83 84 followed by nurses 20 21 26 28 29 37 40 43 46 54 56 60 64. In five studies, the training provided for nurses to perform hearing screening was also briefly mentioned,28 29 40 46 60 including some certifications 56.…”
Section: Resultsmentioning
confidence: 99%
“…Early hearing identification and intervention (EHDI) programs, including universal newborn hearing screening (UNHS), aim to detect hearing loss in infants by three months of age and initiate intervention by six months [ 4 ]. However, UNHS is not widely accessible in Malaysia [ 5 , 6 ]. Therefore, in developing countries like Malaysia, primary care physicians (PCPs) play a crucial role in identifying and intervening for childhood hearing loss as a first point of contact during well-child visits [ 7 ].…”
Section: Introductionmentioning
confidence: 99%